STRATEGI PENGUATAN EKOWISATA DESA TAMBAKMEKAR MELALUI PENDIDIKAN, DAN LITERASI - Anzellica, Angel; Maliq, Anisa Nur'azizah; Wiranto, Arif; Oktavia, Dahlia; Gunari, Davala Gatan Isya (Penerbit Widina, Widina Media Utama, 2025)
Ecotourism plays an important role in environmental conservation, community empowerment, and the improvement of local welfare. Tambakmekar Village in Subang Regency possesses ecotourism potential rooted in its natural and cultural resources, particularly through the presence of Situ Rancalege and the village park; however, its development has not been optimal due to limited facilities, low tourism literacy, and the absence of a well-structured management strategy. Through a 47-day Community Service Program (KKN) by Universitas Subang, a series of participatory activities involving local communities, village officials, schools, and the tourism awareness group (Pokdarwis) were carried out to enhance this potential. The activities included renovating the village park and releasing fish fingerlings in the Situ Rancalege area through collaborative community work as an effort to beautify public spaces and support local food security, conducting creative learning at SDN Pelita Karya using ice-breaking methods to increase student learning motivation, and donating books to the village library in collaboration with the Subang Education and Culture Office to expand knowledge resources and strengthen literacy culture. The implementation of these programs received positive responses from the community, as reflected in increased community participation, improvement in public facilities, enhanced student learning motivation, and the enrichment of village literacy resources. Overall, this program has made a significant contribution to the development of sustainable ecotourism in Tambakmekar Village through environmental conservation, education, and community empowerment.ABSTRAKEkowisata memiliki peran penting dalam pelestarian lingkungan, pemberdayaan masyarakat, dan peningkatan kesejahteraan lokal. Desa Tambakmekar di Kabupaten Subang merupakan wilayah yang memiliki potensi ekowisata berbasis kekayaan alam dan budaya lokal, khususnya melalui keberadaan Situ Rancalege dan taman desa, namun pengembangannya belum optimal akibat keterbatasan fasilitas, rendahnya literasi wisata, dan belum adanya strategi pengelolaan yang terarah. Melalui program Kuliah Kerja Nyata (KKN) Universitas Subang selama 47 hari, dilakukan serangkaian kegiatan berbasis metode partisipatif yang melibatkan masyarakat, perangkat desa, sekolah, dan kelompok sadar wisata (Pokdarwis) untuk memperkuat potensi ekowisata tersebut. Kegiatan yang dilaksanakan mencakup renovasi taman dan penebaran bibit ikan di kawasan Situ Rancalege melalui gotong royong sebagai upaya memperindah ruang publik dan mendukung ketahanan pangan masyarakat, penyelenggaraan pembelajaran kreatif di SDN Pelita Karya menggunakan metode ice breaking untuk meningkatkan motivasi belajar siswa, serta donasi buku ke perpustakaan desa melalui kolaborasi dengan Disdikbud Subang sebagai sarana perluasan wawasan dan penguatan budaya literasi. Pelaksanaan program memperoleh respons positif dari masyarakat yang ditunjukkan melalui peningkatan partisipasi warga, perbaikan kualitas fasilitas publik, tumbuhnya semangat belajar siswa, serta bertambahnya sumber literasi desa. Secara keseluruhan, program ini memberikan kontribusi nyata dalam pengembangan ekowisata berkelanjutan di Desa Tambakmekar berbasis pelestarian lingkungan, pendidikan, dan pemberdayaan masyarakat.